Marine Species at Risk Protection in Australia and Canada: Paper Promises, Paltry Progressions. (2nd July 2016) - Hutchings, Jeffrey A.; Stephens, Tim; VanderZwaag, David L.
ABSTRACT: This article compares the law and policy frameworks for protecting marine species at risk in Australia and Canada. The sea of practical challenges is examined, including achieving listing of threatened commercial species; attaining timely and effective recovery planning; and identifying and protecting critical habitats.